2021
DOI: 10.1002/ieam.4521
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water quality on the macroinvertebrate community in a tropical estuary (Buenaventura Bay)

Abstract: The anthropogenic discharges of inorganic nutrients impact water quality, affecting the macroinvertebrate assemblage and food safety. The main objective of this study was to examine the seawater quality and macroinvertebrate dynamics in muddy habitats of Buenaventura Bay, Colombian Pacific. Macroinvertebrates were captured using artisanal trawl nets during different seasons and along four sampling sites. Multivariate analyses (canonical correspondence analysis and generalized additive model) were used to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 74 publications
1
6
0
5
Order By: Relevance
“…Water quality promotes appropriate ecosystem functioning and supports the generation of ecosystem services which is determined by both biotic and abiotic measures (Foley et al 2015;Pouso et al 2018) and therefore can be characterized by using the concentration ranges of nitrate, chloride, and dissolved oxygen, among other characteristics (Bhateria and Jain 2016;Duque et al 2022). Increased concentrations of productive nutrients like nitrate have been previously linked to anthropogenic practices (Smith 2003;Alonso 2006 andWilkerson andDugdale 2016), such as urban settlements, excess nutrient flow from municipal and agricultural waste which has added pressure on freshwater ecosystem contributing to its deterioration.…”
Section: Influence Of Water Quality On the Abundance Of Prawn Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Water quality promotes appropriate ecosystem functioning and supports the generation of ecosystem services which is determined by both biotic and abiotic measures (Foley et al 2015;Pouso et al 2018) and therefore can be characterized by using the concentration ranges of nitrate, chloride, and dissolved oxygen, among other characteristics (Bhateria and Jain 2016;Duque et al 2022). Increased concentrations of productive nutrients like nitrate have been previously linked to anthropogenic practices (Smith 2003;Alonso 2006 andWilkerson andDugdale 2016), such as urban settlements, excess nutrient flow from municipal and agricultural waste which has added pressure on freshwater ecosystem contributing to its deterioration.…”
Section: Influence Of Water Quality On the Abundance Of Prawn Speciesmentioning
confidence: 99%
“…Increased concentrations of productive nutrients like nitrate have been previously linked to anthropogenic practices (Smith 2003;Alonso 2006 andWilkerson andDugdale 2016), such as urban settlements, excess nutrient flow from municipal and agricultural waste which has added pressure on freshwater ecosystem contributing to its deterioration. Previously, researchers have reported that aquatic systems enriched with nutrients discharged from anthropogenic wastes have influenced the presence and abundance of macroinvertebrate species by subjecting them to low levels of dissolved oxygen and physiological stress (Kenworthy et al 2016;Hale et al 2018;Nelson et al 2019;Ren et al 2019;Duque et al 2022). A low abundance of species was evident in waters with high nitrate, chloride, total dissolved solids and turbidity.…”
Section: Influence Of Water Quality On the Abundance Of Prawn Speciesmentioning
confidence: 99%
“…Estas correlaciones entre la abundancia de recursos pesqueros con las variables sicoquímicas del agua han sido ampliamente estudiadas (Duque et al, 2020;Egertson & Downing, 2011;Gamboa-García et al, 2018a;. Las variables de salinidad, sólidos totales disueltos y transparencia presentaron una correlación negativa con la CPUE total en el trasmallo, lo cual concuerda parcialmente con algunos estudios en el Paci co colombiano en donde se observó que los sólidos totales disueltos están relacionados negativamente con la abundancia y riqueza de los recursos pesqueros; sin embargo, al aumentar la salinidad también incrementó el ensamblaje de macroinvertebrados (Duque et al, 2021).…”
Section: Relación Entre Variables Fisicoquímicas Y El Tipo De Cpueunclassified
“…Desde el punto de vista ecosistémico, el ambiente, la comunidad de organismos y su interacción pueden afectar los rendimientos pesqueros (Defeo, 2015). Por ejemplo, las variables sicoquímicas y de calidad del agua [como nitritos, nitratos, sólidos disueltos totales, pH, oxígeno disuelto y temperatura] pueden afectar la biomasa e intervenir en el conjunto de peces capturados, lo que varía de acuerdo con la zona y la época climática (Duque et al, 2020(Duque et al, , 2021, y, de manera indirecta, puede in uir sobre los porcentajes de captura y sobre la biomasa de interés comercial.…”
Section: Resumen Gráfico 1 Introducciónunclassified
“…Each organism within an ecosystem plays a role in indicating the health of its surrounding environment [4]. The endpoints or biological characteristics zooplankton and benthic macroinvertebrates can be used for water quality assessment such as species number, abundance, biomass, bioindicator, bio-indices [2,5,6]. Razak et al (2019) assessed the water system quality in Malaysia based on the zooplankton structural features [7].…”
Section: Introductionmentioning
confidence: 99%